CHARACTERISTICS OF THE ARAI GRANITE ASSOCIATED WITH THE IRON ORE AND Zn-Cu-Pb DEPOSITS IN MUSI RAWAS REGENCY, SOUTH SUMATERA - Hamdan Zainal Abidin (Jurnal Geologi dan Sumberdaya Mineral, 2010)
The Arai Granite exposed in the Jangkat District, Musi Rawas Regency, South Sumatra. This rock which is in the form of a stock, is assigned to be Cretaceous in age. Petrographical identification shows that this rock is dominated by quartz, feldspar (plagioclase and orthoclase), biotite with minor hornblende, pyroxene and secondary muscovite of holocrystalline- equigranular textures. On the basis of A/CNK ratio (<1.1), the Arai granite belongs to metaluminous type of calc-alkali composition (K2O/Na2O = 0.9-1.06). The Plot of trace elements indicates that this rock belongs to I-type and falls within VAG/SYNCOLG. This granite is intimately associated with subduction of Indian Ocean and Eurasian Plates. It is characterized by strong depletion of Nb, P and Ti significantly. The Arai granite intrudes the Rawas and Peneta Formations of older ages so that lithology of both formations experienced contact metamorphism (marble and hornfels) and mineralization. The presence of iron ore, Zn-Cu-Pb and gold deposits is closely associated with limestone replacement within those formations. Therefore, these deposits are classified into skarn style.Keywords: Arai granite, pluton, Rawas Formation, Peneta Formation, mineralisation, skarn